Quantifying the influence of 5′-RNA modifications on RNA polymerase I activity - Appling, Francis D. (Biophys Chem, 2017)
For ensemble and single-molecule analyses of transcription, the use of synthetic transcription elongation complexes has been a versatile and powerful tool. However, structural analyses demonstrate that short RNA substrates, often employed in these assays, would occupy space within the RNA polymerase. Most commercial RNA oligonucleotides do not carry a 5′-triphosphate as would be present on a natural, de novo synthesized RNA. To examine the effects of 5′-moities on transcription kinetics, we measured nucleotide addition and 3′-dinucleotide cleavage by eukaryotic RNA polymerase I using 5′-hydroxyl and 5′-triphosphate RNA substrates. We found that 5′ modifications had no discernable effect on the kinetics of nucleotide addition; however, we observed clear, but modest, effects on the rate of backtracking and/or dinucleotide cleavage. These data suggest that the 5′-end may influence RNA polymerase translocation, consistent with previous prokaryotic studies, and these findings may have implications on kinetic barriers that confront RNA polymerases during the transition from initiation to elongation.